2012
DOI: 10.1080/09712119.2011.620435
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different levels of Aloe vera gel on ileum microflora population and immune response in broilers: a comparison to antibiotic effects

Abstract: The purpose of the present research is to study the effects of different levels of Aloe vera gel on microflora population, humoral and cellular immune response, and relative weight of lymphoid organs compared to the effects brought about by antibiotic. The groups included the control group (basal diet) as well as three groups with different levels of Aloe vera gel (added to basal diet at 1.5%, 2% and 2.5%), and finally a group with basal diet supplemented by 15 ppm virginiamycin antibiotic. Regarding ileum mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…In recent years, several studies concerning AV products use in broilers have arisen; however, results are somehow contradictory and some topics remain unstudied, such as the effect of AV powder on broiler intestinal morphology (Mmereol ; Darabighane et al . ). To our knowledge, this is the first study to investigate the comparative effect of synbiotic, antibiotic and AV supplementation on the growth performance, gut morphology, immunity, hematology and blood biochemistry of broilers.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, several studies concerning AV products use in broilers have arisen; however, results are somehow contradictory and some topics remain unstudied, such as the effect of AV powder on broiler intestinal morphology (Mmereol ; Darabighane et al . ). To our knowledge, this is the first study to investigate the comparative effect of synbiotic, antibiotic and AV supplementation on the growth performance, gut morphology, immunity, hematology and blood biochemistry of broilers.…”
Section: Discussionmentioning
confidence: 97%
“…[46] reported significantly higher anti-SRBC antibody (total immunoglobulins [Igs], IgG and IgM) titers in chickens supplemented with ethanolic extract of AV as compared with the control group. Results of another trial revealed significantly higher humoral immune responses against SRBC and NDV in chickens supplemented with 2.5% AV gel in diet [47]. Likewise, Valle-Paraso et al .…”
Section: Discussionmentioning
confidence: 99%
“…Akhtar et al (2012) reported that ethanolic and aqueous extracts of Aloe vera improved antibody titers against SRBC, whereas addition of Aloe vera to drinking water at a level of 2% improved antibody titers against NDV (Valle-Paraso et al, 2014). Furthermore, Akhtar et al (2012) and Darabighane et al (2012) reported similar positive effects on cellular immunity. The improvement in the immune system performance may be attributed to acemannan, a polysaccharide contained in Aloe vera.…”
Section: Discussionmentioning
confidence: 56%